Isolation of Multidrug-Resistant Mycobacterium Avium Subsp. Avium from a Wild Eurasian Otter (Lutra Lutra) - Irena Reil; Sanja Duvnjak; Silvio Špičić; Gordan Kompes; Antonela Bagarić; Martina Đuras; Andrea Gudan Kurilj; Maja Lukač; Mišel Jelić; Maja Zdelar-Tuk (MDPI AG, 2024)
Mycobacterium avium subsp. avium is pathogenic mainly to birds, although cases of mycobacteriosis caused by these bacteria have also been reported in other animals and humans. Not much is known about the effects of this pathogen on otters. The aim of this study was to report for the first time the isolation of M. avium subsp. avium in wild otter and to describe its multidrug resistance profile. A female otter injured in a car accident was found dead and subjected to postmortem examination. Apart from the trauma changes, no other macroscopic pathological changes were detected. Bacteriologic examination revealed the presence of acid-fast bacilli in the lymph nodes, which were confirmed by molecular methods as M. avium subsp. avium. Antimicrobial susceptibility testing revealed susceptibility to clarithromycin and amikacin, but resistance to linezolid, moxifloxacin, streptomycin, isoniazid, trimethoprim/sulfamethoxazole, ciprofloxacin, doxycycline, and ethionamide. This is unusual for wild species, which generally should not come into contact with antimicrobials, and may suggest that multidrug-resistant MAC strains are circulating between wild and domestic animals. These results emphasise the need for additional epidemiological studies on non-tuberculous mycobacteria in wildlife and their implications for one health.